Global burden of thyroid cancer and its attributable risk factors in 204 countries and territories from 1990 to 2019. Issue 18 (5th August 2021) - Bao, Wen‐Qi; Zi, Hao; Yuan, Qian‐Qian; Li, Lu‐Yao; Deng, Tong
Abstract: Background: To investigate the burden of thyroid cancer and its attributable risk factors in 204 countries and territories during 30 years. Methods: We extracted data from the Global Burden of Disease (GBD) 2019 database, including incidence, mortality, disability‐adjusted life‐years (DALYs), and the attributable risk factors of thyroid cancer from 1990 to 2019. Estimated annual percentage changes (EAPC) were calculated to assess the changes in age‐standardized incidence rate (ASIR), age‐standardized mortality rate (ASMR), and age‐standardized DALYs rate (ASDR). We also examined the associations between cancer burden and the sociodemographic index (SDI). Results: The global new cases, death, and DALYs of thyroid cancer in 2019 were 233 847 (95% UI: 211 637–252 807), 45 576 (95% UI: 41 290‐48 775), and 1 231 841 (95% UI: 1 113 585–1 327 064), respectively. From 1990 to 2019, the ASIR of thyroid cancer showed an upward trend (EAPC = 1.25), but ASMR (EAPC = −0.15) and ASDR (EAPC = −0.14) decreased. The burden of thyroid cancer varied at regional and national levels, but the association between ASIR and SDI was positive. We found that the burden of thyroid cancer was mainly concentrated in females and that the age of onset tended to be younger. The proportion of DALYs from thyroid cancer attributable to high body‐mass index was higher in high SDI regions, especially in males. Conclusions: The global incidence of thyroid cancer has continued to increase in the past three decades. The high body‐mass index as an important risk factor for thyroid cancer deserves greater attention, especially in high SDI regions. Abstract : The burden of thyroid cancer varies in 204 countries and territories from 1990 to 2019. The global incidence of thyroid cancer (a) has increased significantly, while the mortality (b) and DALYs (c) have decreased in the past three decades.